COMPARATIVE ANALYSIS OF PERFORMANCE OF ISLAMIC BANKS AND CONVENTIONAL BANKS: RISKS AND OPPORTUNITIES (Ta'limning zamonaviy transformatsiyasi, 2024)
This comprehensive analysis explores the distinct opportunities and risk profiles of Islamic and conventional banks, focusing on their principles, market strategies, and growth potentials. Islamic banks, operating under Sharia principles, emphasize ethical finance, risk-sharing, and asset-backed transactions. These banks have significant growth opportunities due to their appeal to ethically-minded investors and the large unbanked Muslim population. Conventional banks, which operate on interest-based transactions and profit maximization, also face diverse opportunities driven by technological advancements and globalization. The analysis highlights the distinct opportunities and challenges faced by Islamic and conventional banks. Islamic banks have significant potential to grow by catering to ethical finance demands and the unbanked Muslim population, while conventional banks can leverage technological advancements and globalization. Understanding these opportunities and risk profiles allows stakeholders to make informed decisions and strategically navigate the evolving financial landscape.